Hybrid Disturbance Response Decoupling for Multivariable Systems - Wang, Fu-Cheng; Lee, Chung-Hsien (IEEE transactions on automatic control, 2024)
This article proposes a novel control theorem called hybrid disturbance response decoupling (HDRD), which facilitates the independent and simultaneous modification of all transmission paths of a multivariable system. The control design for multivariable systems is challenging because feedback controllers can usually affect all the transmission paths concurrently. Improving the performance of some transmission paths might sacrifice the performance of others; therefore, the disturbance response decoupling theorem was proposed to keep specific transmission paths unchanged while improving others. However, an independent and concurrent control design for all transmission paths remains unavailable. This article proposes the HDRD theorem, which permits independent control designs for multiple transmission paths and integration without cross influences. Finally, numerical examples are applied to demonstrate the effectiveness and feasibility of the proposed HDRD theorem for multivariable systems.